Increasing resilience of the UK fresh fruit and vegetable system to water-related risks - Zurek, Monika; Garbutt, George; Lieb, Theresa; Hess, Tim M.; Ingram, John (MDPI, 2020)
The many economic, regulatory and environmental pressures on growing, processing, distributing and retailing UK-produced fresh fruit and vegetables (FF&V) are managed by a complex set of actors before reaching the consumer. Much of this production takes place in the driest parts of the country which are characterised as “water scarce”. While physical risk is a key component of water-related risks to growers, different actors in the system face other types of risk, such as supply chain risks, food safety risks, reputational risks and/or regulatory risks. In this paper we reveal how different types of actors in the UK FF&V system perceive and frame water-related risks, what risk management strategies they employ and how they envision a FF&V system more resilient to water-related risks. Using interviews with actors from across the system, as well as governmental and nongovernmental actors influencing the system, we unpack the complex nature of the FF&V system. This provides insights into the different ways system actors assemble around water-risk and highlights that, if resilience-building activities at the individual actor level are not coordinated, there is a high risk that they are undermining overall system resilience
Keywords: food system actors; resilience; water risk; fresh fruit and vegetable systems